2017
DOI: 10.25170/balance.v14i2.73
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Persentase Kepemilikan Asing, Latar Belakang Pendidikan Komite Audit, Ukuran Kap, Umur Perusahaan, Profitabilitas, Dan Solvabilitas Terhadap Audit Delay

Abstract: The purpose of this research is  to analyze the effect of foreign ownership percentage, audit committee education background, size of public accounting firm, company age, profitability and solvency to audit delay in mining companies that listed in Indonesia Stock Exchange (IDX). This study takes company samples in 2011 - 2015. This research uses data from the Fact Book and the company's financial statements. The total sample in this research are 80 companies during 2011 - 2015. The significance value used in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Results are in line with the results of (Lienardi & Widyastuti, 2017) from the results of the research it is concluded that companies that have been around for a long time will have more experience so that their internal control system becomes better. The older the company, the more ability to collect, process, and produce the information needed by the auditor to support the audit process more effectively and efficiently so that the audit time can be faster.…”
Section: The Effect Of Company Age On Audit Delaysupporting
confidence: 85%
See 1 more Smart Citation
“…Results are in line with the results of (Lienardi & Widyastuti, 2017) from the results of the research it is concluded that companies that have been around for a long time will have more experience so that their internal control system becomes better. The older the company, the more ability to collect, process, and produce the information needed by the auditor to support the audit process more effectively and efficiently so that the audit time can be faster.…”
Section: The Effect Of Company Age On Audit Delaysupporting
confidence: 85%
“…Then, research on audit delay influenced by the company's solvency obtained inconsistent results, an argument from Harjanto (2017) and (Lienardi & Widyastuti, 2017) it is stated that Audit Delay is not affected by Company solvency. Meanwhile, argument from (Saputra et al, 2020) it is stated that Audit Delay is affected by the Company's Solvency.…”
Section: Introductionmentioning
confidence: 99%
“…Companies listed on the IDX during the 2015-2019 period were 2,881 observations. The final sample is 356 companies for 5 years and produces 1,780 observations based on several predetermined criteria (Lara et al, 2009;Lienardi & Widyastuti, 2017).…”
Section: Population and Samplementioning
confidence: 99%